Periodic Mesoporous Organosilicas as Efficient Nanoreactors in Cascade Reactions Preparing Cyclopropanic Derivatives. Issue 9 (21st March 2019) - Huo, Hang; Jiang, Yanqiu; Zhao, Tingting; Wang, Junlei; Li, Defeng; Xu, Xianzhu; Lin, Kaifeng
Abstract: In this work, three organosilica precursors functionalized with carbamate moieties were synthesized by condensing of 3‐isocyanatopropyltriethoxysilane and coupling regents of either hydroquinone (HQ), bisphenol A (BPA), or 1, 1′‐bi‐2‐naphthol (BN). These organosilica precursors were covalently bonded in the framework of periodic mesoporous organosilicas by co‐condensation and hydrolysis with tetraethyl orthosilicate (TEOS) under hydrothermal treatment. The compositions and physical properties were characterized with FTIR, XRD, thermogravimetric/differential thermal analysis (TG/DTA), 29 Si NMR, 13 C NMR spectroscopies, SEM, TEM, and BET technologies. These characterizations suggest that three different structures were formed as the result of different sizes and compositions of the organosilica precursors. The three mesoporous organosilicas were applied as heterogeneous catalysts in the one‐pot cascade Knoevenagel and Michael cyclopropanic reactions for the synthesis of cyclopropanic derivatives and showed excellent activity and selectivity. The highest conversion was obtained with mesoporous catalyst (MC)‐HQ owing to its ordered mesostructure, highest surface area, and weakest stereo effect of the organic linking groups compared with MC‐BAP and MC‐BN. This methodology employed cheaper and more easily obtainable raw materials as reagents over the traditional alkene additive system and these heterogeneous catalysts exhibit superior performance and recyclability than typical homogeneous organic catalysts. Abstract : Nanoreactors in cascade : Three carbamate‐functionalized organosilicas were covalently incorporated into the framework of mesoporous silica, and these materials exhibited excellent catalytic performance toward heterogeneous Knoevenagel and Michael cyclopropanic cascade reactions.